Pengaruh Kualitas Produk, Store Asmosphere, dan Kualitas Layanan, Terhadap Kepuasan Konsumen Di Starbucks Gajah Mada Semarang - Wibowo, Vera Angelina; Athanasius, Sentot Suciarto (Universitas Katolik Soegijapranata, Semarang, 2025)
Efforts to differentiate themselves from others in the coffee shop business make business people try to do something different from other coffee shops. This study aims to determine the effect of product quality, store atmosphere, and service quality on consumer satisfaction at Starbucks Gajah Mada Semarang. The method used is a quantitative method with a non-probability sampling design using a purposive sampling technique. The total respondents in this study were 96 people. The results of the study indicate that product quality, store atmosphere, and service quality have a positive and significant effect on consumer satisfaction at Starbucks Gajah Mada Semarang. It is hoped that the results of the research that has been conducted at Starbucks Gajah Mada Semarang can provide value or benefits that exceed consumer expectations so that consumers can always feel satisfied.